Enhancing Toxicology Achievement by the VARK and the GRSLSS-mixed Models in Team-Based Learning - Khamphaya, Tanaporn; Pouyfung, Phisit; Yimthiang, Supabhorn (Frontiers in Public Health, 2022)
Toxicology is needed to implement in occupational health and safety (OHS) curriculum. Teaching toxicology is very challenging as its multidisciplinary science. Keeping students engaged in learning is a difficult issue when introducing solely theoretical framework. To enhance student performance, educators need to be aware of different learning styles and teach students accordingly. This study aimed to examine preferred learning styles and to further investigate the impact of learning style on team allocation and the effectiveness of TBL in toxicology. A cross-sectional study of occupational health and safety students was performed. The VARK (visual, aural, reading/writing, and kinesthetic) learning style questionnaire and the Grasha Reichmann Student Learning Styles Scale (GRSLSS), which identifies independent, dependent, collaborative, participant, competitive, and avoidant learning styles, were used with 101 study participants. After classification, participants studied three aspects of toxicology in three respective situations: i) individual learning, ii) team-based learning with students of the same VARK learning style, and iii) team-based learning with students of varying VARK learning styles. Afterwards, participants wrote a test on each of the aspects. The dominant VARK and GRSLSS learning styles were reading/writing (33.33%) and collaborative (50%), respectively. The participants achieved the highest test scores (average 88.31%) when they studied in a team with various VARK styles, followed by studying in a team with the same VARK style (83.43%). Individual learning produced the lowest average score (69.79%). The results of this study suggest that creating a successful heterogeneity team based on the preferred learning styles is effective teaching method in toxicology. It might be useful to toxicology educators, and researches from a wide range of disciplines to enhance student performance.